Current Awareness Services of the UP Main Library factor affecting the awareness of and utilization by users and implementation by librarians - Lanuza, Jonathan F.; Santos, Yhna Therese P. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2013)
Academic libraries remain as the only information centers of the university and keeping the users informed and updated is a critical function that the library must fulfil. The study focuses on the top mechanism for this function, Current Awareness Services, and the factors that affect the awareness and utilization of users and the implementation of the librarians. The research studied the users and the librarians of the UP Main Library.
The study surveyed a total of 98 users using a systematic random sampling method and the librarian using survey questionnaires specified for each. The survey for users looked for different user perception and need on CAS and the problems and suggestion they can give.
Analyzing the data, users currently are more inclined to find out, learn, and use CAS on their own and less likely to acquire it from the promotional activities of the library or from the librarians themselves. Relating to this data, users use the library more for personal activities and use less of the materials promoted like journals and research publication and more of the facilities like Internet.
The study reveals that users express great need for the services and find it very suitable for their needs but the services' availability, updatedness and ease of use rated relatively low with the users.
The study suggests that the promotion and marketing of the services is the top recommendation to improve the services further because the library already provides the information need of the users, they just need to market and teach.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) Main Library; Current awareness services -- Philippines -- Quezon City